1985
DOI: 10.1182/blood.v66.4.848.848
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the Hodgkin's disease associated antigen Ki-1 in reactive and neoplastic lymphoid tissue: evidence that Reed-Sternberg cells and histiocytic malignancies are derived from activated lymphoid cells

Abstract: Ki-1 is a monoclonal antibody (raised against a Hodgkin's disease- derived cell line) that, in biopsy tissue affected by Hodgkin's disease, reacts selectively with Reed-Sternberg cells. The expression of Ki-1 antigen has been analyzed by immunocytochemical techniques in a wide range of human tissue and cell samples, including fetal tissue, malignant lymphomas (290 cases), and mitogen- and virus-transformed peripheral blood lymphocytes. The antigen was detectable on a variable proportion of cells in all cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
372
2
14

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,188 publications
(395 citation statements)
references
References 34 publications
7
372
2
14
Order By: Relevance
“…Ki-1 (CD30) positive anaplastic large cell lymphoma (ALCL), first described as a distinct morphological entity by Stein et al (1985), was found to be associated with the translocation t(2;5)(p23;q35) in 30-40% of cases (Le Beau et al, 1989;Mason et al, 1990). By classic cytogenetics, it was also possible to detect the t(2;5) in the small-cell predominant variant of ALCL (Kinney et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Ki-1 (CD30) positive anaplastic large cell lymphoma (ALCL), first described as a distinct morphological entity by Stein et al (1985), was found to be associated with the translocation t(2;5)(p23;q35) in 30-40% of cases (Le Beau et al, 1989;Mason et al, 1990). By classic cytogenetics, it was also possible to detect the t(2;5) in the small-cell predominant variant of ALCL (Kinney et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their classical ribosome-inactivating glycosidase activity, other activities and enzymatic properties were associated with RIPs: antiviral activity [265], depurination of (non-ribosomal) RNA and adenine DNA glycosylase activity [266][267][268][269][270], deoxyribonuclease activity [271][272][273][274][275][276][277][278], ribonuclease activity [279,280], removal of adenine from poly(ADP-ribosyl)ated poly(ADP-ribose) polymerase (an enzyme involved in DNA repair) [281,282], depurination of the capped RNA template [283,284], superoxide dismutase (SOD) activity [285][286][287] and phospholipase activities [288]. The involvement of these non-classical RIP activities in cytotoxicity is debatable, though accumulating evidence suggests that ribosome inactivation is not the sole means by which RIPs execute their toxic effects [264,[289][290][291][292][293][294][295] CD25 and CD30 are lymphoid activation markers which are highly expressed on the surface of Hodgkin's lymphoma cells and only present on a minority of normal human cells [135,[296][297][298]. In order to target these cells, two immunotoxins, RFT5-dgA (IMTOX25) and ki-4.dgA, were constructed.…”
Section: Ribosome Inactivating Proteins-mechanism Of Actionmentioning
confidence: 99%
“…Primary cutaneous anaplastic large cell lymphoma in an elderly patient with cryoglobulinaemic hepatitis C virus infection DOI: 10.1111/j. 1365-2133.2004.06232.x SIR, CD30+ or Ki-1+ anaplastic large cell lymphoma (ALCL) is a rare form of non-Hodgkin's lymphoma (NHL) first described by Stein et al 1 It has a distinctive pleomorphic appearance, sinusoidal growth pattern, and reactivity with the CD30 antibody. ALCL may be classified according to the location of the original tumour: primary nodal, primary cutaneous or secondary cutaneous.…”
mentioning
confidence: 99%
“…ALCL was defined by a frequent cohesive proliferation of large pleomorphic blasts and constant expression of the CD30 molecule in all neoplastic cells. 1 These proliferations first arise in lymph nodes in most cases but may involve other parts of the body, especially the skin, as a primary site. 8 Recently recognized cytogenetic and immunophenotypic differences confirm the clinical evidence that primary nodal and primary cutaneous ALCL are distinct entities.…”
mentioning
confidence: 99%
See 1 more Smart Citation